Development of rapid and effective oil-spill response system integrated with oil collection, recovery and storage devices for small oil spills at initial stage: From lab-scale study to field-scale test - Piao, Linfeng; Park, Chan Jin; Kim, Seongjin; Park, Kyungtaek; Lee, Yongjun; Kim, Ho-Young; Moon, Myoung-Woon; Park, Hyungmin (Academic Press, 2023)
In the present study, through the laboratory-to-field scale experiments and trials, we report the development and evaluation of an integrated oil-spill response system capable of oil collection, recovery (separation), and storage, for a timely and effective response to the initial stage of oil-spill accidents. With the laboratory-scale experiments, first, we evaluate that the water-surface waves tend to abate the oil recovery rate below 80% (it is above 95% for the optimized configuration without the waves), which is overcome by installing the hydrophilic (and oleophobic) porous structures at the inlet and/or near the water outlet of the separator. In the follow-up meso-scale towing tank tests with a scaled-up prototype, (i) we optimize the maneuverability of the assembled system depending on the speed and existence of waves, and (ii) evaluate the oil recovery performance (more than 80% recovery for the olive oil and Bunker A fuel oil). Although more thorough investigations and improvements are needed, a recovery rate of over 50% can be achieved for the newly enforced marine fuel oil (low sulfur fuel oil, LSFO) that was not targeted at the time of development. Finally, we perform a series of field tests with a full-scale system, to evaluate the rapid deployment and operational stability in the real marine environment. The overall floating balance and coordination of each functional part are sustained to be stable during the straight and rotary maneuvers up to the speed of 5 knots. Also, the collection of the floating debris (mimicking the spilled oil) is demonstrated in the field test. The present system is now being tested by the Korea Coast Guard and we believe that it will be very powerful to prevent the environmental damage due to the oil spills.